Pharmacokinetics, Safety, and Tolerability of Orally Administered Ursodeoxycholic Acid in Patients With Parkinson's Disease—A Pilot Study. (12th February 2020) - Sathe, Abhishek G.; Tuite, Paul; Chen, Chi; Ma, Yiwei; Chen, Wei; Cloyd, James; Low, Walter C.; Steer, Clifford J.; Lee, Byeong‐Yeul; Zhu, Xiao‐Hong; Coles, Lisa D.
Abstract: Mitochondrial dysfunction is implicated in the pathogenesis of Parkinson's disease. Preliminary data have shown lower brain adenosine triphosphate (ATP) levels in Parkinson's disease versus age‐matched healthy controls. Ursodeoxycholic acid (UDCA) may improve impaired mitochondrial function. Our objective was to evaluate UDCA tolerability, pharmacokinetics, and its effect on brain bioenergetics in individuals with Parkinson's disease. An open‐label, prospective, multiple‐ascending‐dose study of oral UDCA in 5 individuals with Parkinson's disease was completed. A blood safety panel, plasma concentrations of UDCA and UDCA conjugates, and brain ATP levels were measured before and after therapy (week 1: 15 mg/kg/day; week 2: 30 mg/kg/day; and weeks 3‐6: 50 mg/kg/day). UDCA and conjugates were measured using liquid chromatography–mass spectrometry. ATP levels and ATPase activity were measured using 7‐Tesla 31 P magnetic resonance spectroscopy. Secondary measures included the Unified Parkinson's Disease Rating Scale and Montreal Cognitive Assessment. UDCA was generally well tolerated. The most frequent adverse event was gastrointestinal discomfort, rated by subjects as mild to moderate. Noncompartmental pharmacokinetic analysis resulted in (mean ± standard deviation) a maximum concentration of 8749 ± 2840 ng/mL and half‐life of 2.1 ± 0.71 hr. Magnetic resonance spectroscopy data were obtained in 3 individuals with Parkinson's disease and showed modest increases in ATP and decreases in ATPase activity. Changes in Unified Parkinson's Disease Rating Scale (parts I‐IV) and Montreal Cognitive Assessment scores (mean ± standard deviation) were –4.6 ± 6.4 and 2 ± 1.7, respectively. This is the first report of UDCA use in individuals with Parkinson's disease. Its pharmacokinetics are variable, and at high doses it appears reasonably well tolerated. Our findings warrant additional studies of its effect on brain bioenergetics.